Buying a House in Colombia from France: Migratory Project and Transnational Actions “From Below” - Ardila, Marcia (Universidad del Rosario, 2019)
This article explores transational practices of Colombian migrants which convey in the purchase of real estate in Colombia from France. The mobilization of social and economic resources among migrants and their close circles will be analyzed, as well as the representations and expectations that are built around the acquisition of housing. These houses, which are not yet physically inhabited by migrants - and possibly will never be - are of great symbolic importance in the migratory project: They give meaning to the road travelled, with their sacrifices and obstacles, and they constantly update the medium and long-term projections regarding a probable return to the country of origin. Different questions structure the analysis: How is the purchase of housing inscribed in the individual and family migration project? In what ways are non-migrants involved in the purchase and subsequent maintenance of the property? To what extent do resourcefulness actions, embedded in transnational social networks, facilitate the production and circulation of the necessary economic capital to carry out the transaction?